Lanthanum Strontium Cobalt Ferrite-Copper Oxide As Cathode For Intermediate Temperature Solid Oxide Fuel Cell - Mohd Abd Fatah, Ahmad Fuzamy (2018)
Solid oxide fuel cells (SOFCs) are the efficient yet environmentally benign devices that can convert chemical energy into electrical energy and heat for large scale applications. However, high operating temperature of this device limits the selection of proper materials to be used as electrode and electrolyte as well as sacrifices the durability. Thus, it is desirable to develop materials with superior electrochemical performance at intermediate temperature (600-900 'C) for SOFC. LSCF doped with CuO is an attractive yet promising cathode material for IT-SOFC owing to its distinguished properties including high electrical conductivity and high catalytic activity for the oxygen reduction reaction. This study was devoted to investigate the influence of the synthesis routes, which are solid state route and sol-gel route toward chemical, physical and electrochemical properties of composite LSCF-CuO. The samples were synthesised at different temperatures ranging from 600 'C to 900 'C for each route, respectively. XRD results showed high purity of as-synthesised samples while in the meantime, increase in crystallinity was observed as the calcining temperature increases, indicating bigger crystal size after calcined at 900 'C. SEM images showed that the LSCF-CuO particles tend to expand as the calcining temperature increases. Meanwhile, from the TGA results, it was clear that the LSCF-CuO has significantly loss its weight after calcined at designed temperatures (600 'C, 700 'C, 800 'C, 900 'C). LSCF-CuO showed promising electrochemical properties than LSCF and the polarisation resistance obtained from LSCF-CuO synthesised using sol-gel method was much lower compared to that of solid state method. Moreover, it was found that reducing calcining temperature can greatly influence the electrochemical performance, which was in line with characterisation results. EIS analysis also showed that addition of copper oxide toward LSCF type cathode greatly enhanced the performance as the LSCF-CuO type cathode produced much lower polarization resistance as compared to pure LSCF type cathode.